Pelvic floor disorders: Case study - Flood, Catherine (Canadian Urological Association Journal, 2013)
Interactive case study discussions were an integral part of the program at the 3rd Annual Canadian Urology Forum (2013). The following is a summary of discussions pertaining to a case illustrating the difficulties in the management of pelvic floor disorders.